2018
DOI: 10.1016/j.ajur.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Management of complex and redo cases of pelvic fracture urethral injuries

Abstract: ObjectivesPelvic fracture urethral injuries (PFUI) result from traumatic disruption of the urethra. A significant proportion of cases are complex rendering their management challenging. We described management strategies for eight different complex PFUI scenarios.MethodsOur centre is a tertiary referral centre for complex PFUI cases. We maintain a prospective database (1995–2016), which we retrospectively analysed. All patients with PFUI managed at our institute were included.ResultsOver two decades 1062 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…We found that a history of pelvic angioembolization at the time of injury was a significant risk factor for surgical failure. While this is the first study to document this risk, arterial insufficiency has previously been identified as a risk factor for failure and some have advocated using preoperative penile Doppler ultrasound assessment in high-risk patients to evaluate arterial integrity and potential need for penile revascularization prior to urethroplasty [16][17][18][19][20]. While the data presented here do show that angioembolization is associated with an increased rate of urethroplasty failure, the present study did not specifically assess the role of preoperative Doppler assessment or revascularization in predicting failures.…”
Section: Acute Managementmentioning
confidence: 99%
“…We found that a history of pelvic angioembolization at the time of injury was a significant risk factor for surgical failure. While this is the first study to document this risk, arterial insufficiency has previously been identified as a risk factor for failure and some have advocated using preoperative penile Doppler ultrasound assessment in high-risk patients to evaluate arterial integrity and potential need for penile revascularization prior to urethroplasty [16][17][18][19][20]. While the data presented here do show that angioembolization is associated with an increased rate of urethroplasty failure, the present study did not specifically assess the role of preoperative Doppler assessment or revascularization in predicting failures.…”
Section: Acute Managementmentioning
confidence: 99%
“…Twenty-two studies described the use of anastomotic end-to-end urethroplasty in 893 patients (Table 1). AU was used to treat anterior strictures in 32% ( n = 7) [11, 14, 17, 18, 20, 25, 29], posterior strictures in 45% ( n = 10) [13, 15, 19, 23, 26, 2830, 45, 46] and mixed bulbo-membranous strictures in 14% ( n = 3) [15, 27, 29] of the studies which were reviewed. Five studies ( n = 5) [12, 16, 21, 22, 24] did not provide information on the location of the stricture.…”
Section: Resultsmentioning
confidence: 99%
“…Overall success rates vary widely across studies at 0–100%. When assessing its use to specific locations, anastomotic urethroplasty fared best when utilised in anterior bulbar and posterior recurrent strictures [11, 13, 14, 1720, 23, 25, 27–29, 45, 46]. The success rates were reported as 58–100% and 68.7–100%, respectively, for these cohorts of patients, with four studies reporting success rates of 100% in anterior bulbar strictures.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst many of these patients have an idiopathic aetiology, it is well recognised that inflammatory changes and in particular trauma can result in catastrophic damage to the urethra. Pelvic fracture injuries are an important cause of significant damage to the posterior urethra and this is reviewed in detail by Sanjay B. Kulkarni and colleagues [3] and Yumeng Zhang and colleagues [4] . The contemporary management of anterior urethral stricture disease is summarised by Li Cheng and colleagues [5] .…”
mentioning
confidence: 99%